Understanding the Drivers of Eco-Innovation Efficiency: A Systematic Overview - Oussama, Selorm; Oluyede, Njeru (Journal of Policy Options, 2022)
Eco-innovation is a central focus of European Union policy, playing a critical role not only for individual companies but also for entire economic systems. Given the multitude of factors that drive eco-innovation, this research aims to identify the key determinants that influence the efficiency of eco-innovation efforts. The study was conducted using a systematic literature review, employing the SALSA method to ensure a thorough and structured analysis. The research focused on examining publications from the Scopus database, ultimately reviewing 469 selected papers. A rigorous appraisal process was used to identify studies that specifically addressed the determinants of eco-innovation efficiency. The literature review identified a total of 24 determinants that influence the efficiency of eco-innovation. These determinants were further categorized based on two criteria. The first criterion distinguishes between cost-related and revenue-related determinants, highlighting the financial aspects that impact eco-innovation efficiency. The second criterion differentiates between strategic and operational levels, emphasizing the various managerial and organizational factors that play a role in the successful implementation of eco-innovation. It is important to note that eleven publications were excluded from the research due to issues of incompletion or inaccessibility, ensuring that the analysis was based on high-quality and relevant studies. The findings underscore the importance of stimulating eco-innovation across all companies. By providing a comprehensive set of determinants that affect eco-innovation efficiency, this research offers valuable insights for executives and policymakers. Understanding these determinants will enable better management and strategic planning, ultimately enhancing the effectiveness of eco-innovation initiatives and contributing to more sustainable business practices. The study not only identifies key factors influencing eco-innovation efficiency but also provides a framework that can support decision-makers in fostering eco-innovation, thereby aligning with broader European Union sustainability goals.